Distinct roles of E2F proteins in vascular smooth muscle cell proliferation and intimal hyperplasia - Giangrande, Paloma H. (National Academy of Sciences, 2007)
Intimal hyperplasia (IH) and restenosis limit the long-term utility of bypass surgery and angioplasty due to pathological proliferation and migration of vascular smooth muscle cells (VSMCs) into the intima of treated vessels. Consequently, much attention has been focused on developing inhibitory agents that reduce this pathogenic process. The E2F transcription factors are key cell cycle regulators that play important roles in modulating cell proliferation and cell fate. Nonselective E2F inhibitors have thus been extensively evaluated for this purpose. Surprisingly, these E2F inhibitors have failed to reduce IH. These findings prompted us to evaluate the roles of different E2Fs during IH to determine how selective targeting of E2F isoforms impacts VSMC proliferation. Importantly, we show that E2F3 promotes proliferation of VSMCs leading to increased IH, whereas E2F4 inhibits this pathological response. Furthermore, we use RNA probes to show that selective inhibition of E2F3, not global inhibition of E2F activity, significantly reduces VSMC proliferation and limits IH in murine bypass grafts.